Utilization of a novel 3D radiologic scoring method to define therapeutic response and surgical candidacy - Rahmanuddin, Syed; Von Hoff, Daniel D.; Chaudhry, Ammar; Guidaben, Danielle; Khan, Marjaan; Boswell, William; Cridebring, Derek; Brase, Jordyn; Fong, Yuman; Motarjem, Pejman; Borazanci, Erkut (Frontiers in Imaging, 2023)
Purpose: The aim of this study is to define a novel CT perfusion analytical method by observing the treatment response of pancreatic cancer patients in a neoadjuvant treated population to determine surgical candidacy. Experimental Design: Our study involved 22 adult patients with pancreatic ductal adenocarcinoma (PDAC). Participants received neoadjuvant therapy (paricalcitol, paclitaxel protein bound, cisplatin and gemcitabine) for up to 6 months. The study examined differences in density between the arterial and venous phases of CT scans using a mathematical analysis called the Marley equation. The data was used to assess treatment responses and determined whether a patient can become a surgical candidate. The consideration for surgical candidacy was defined by Dr. Rahmanuddin termed the “R” score graphically depicted as the “R” Clock. The R score determined the number of tumor-linked blood vessels. Any vessel associated with tumor involvement received a score of 1. Patients who received a score of 5 or less were eligible for surgery. 3D Tumor volumetric analyses were performed using GE AW 3D software to assess the treatment response associated with tumor perfusion. Results: Visual differences in vascular involvement between baseline and final imaging was associated with a higher likelihood of proceeding to surgery. After administration of the neoadjuvant therapy, 81% of patients (18 of 22) received an R score of 5 or less deeming the all of them eligible for surgery. 59% of patients (13 of 22) proceeded with the surgery. Changes in arterial and venous perfusion reflected tumor aggressiveness as defined by the Marley equation. Conclusion: CT vessel perfusion using the R score and Marley Equation might be helpful in defining the surgical candidacy of PDAC patients when used in conjunction with 3D tumor volumetric quantification. The parameters defined by the R score determined higher perfusion scores as having greater vascular growth, and patients with tumor involvement of more than 6 vessels were deemed surgically unresectable. The Marley equation demonstrated tumor aggression via changes in arterial and venous perfusion. Additional studies are needed to further validate these methodologies and assess the clinical utility.